Informativity of sentence information structure : the role of word order - Peti-Stantić, Anita (Array, 2014)
Halliday’s (1967) introduction of the term information structure virtually initiated the research on semantic relationships between sentence structure elements based on the discursive position of an utterance. His work has greatly contributed to the defining of information structure as a formal element in the pragmatic structuring of propositions in the discourse (Lambrecht 1994) in terms of the relationships between linguistic tools and circumstances on the one hand and/or speaker’s intentions on the other. Given that the analysis of this relationship is almost entirely novel to Slavic linguistics, I intend to present some new data on the clitic and clitic cluster positioning in the linear order of Croatian sentences. I will offer an account of the basic features of the multi-leveled approach to the analysis of examples containing clitics and clitic clusters, which will allow for the establishment of criteria to classify sentences as unmarked or marked from the point of view of information structure. The premise underlying the work reported here is that information structure is part of the conceptual structure. Within the Theory of Parallel Architecture (Jackendoff 2002), conceptual structure is the component of grammar that enters into a systematic relationship with the units of the phonological and syntactic component, determining the informational potential of the sentence. The empirical part presents preliminary research results on the relationship between the placement of clitics and clitic clusters and the information structure in Croatian, a so- called “free word-order” language. The goal of this study is to set the ground for establishing the constraints to the combinatorial properties of clitic and clitic cluster units and the hierarchy among them.